3D Bioprinting of Engineered Tissue Flaps with Hierarchical Vessel Networks (VesselNet) for Direct Host‐To‐Implant Perfusion. Issue 42 (12th September 2021) - Szklanny, Ariel A.; Machour, Majd; Redenski, Idan; Chochola, Václav; Goldfracht, Idit; Kaplan, Ben; Epshtein, Mark; Simaan Yameen, Haneen; Merdler, Uri; Feinberg, Adam; Seliktar, Dror; Korin, Netanel; et al.
Abstract: Engineering hierarchical vasculatures is critical for creating implantable functional thick tissues. Current approaches focus on fabricating mesoscale vessels for implantation or hierarchical microvascular in vitro models, but a combined approach is yet to be achieved to create engineered tissue flaps. Here, millimetric vessel‐like scaffolds and 3D bioprinted vascularized tissues interconnect, creating fully engineered hierarchical vascular constructs for implantation. Endothelial and support cells spontaneously form microvascular networks in bioprinted tissues using a human collagen bioink. Sacrificial molds are used to create polymeric vessel‐like scaffolds and endothelial cells seeded in their lumen form native‐like endothelia. Assembling endothelialized scaffolds within vascularizing hydrogels incites the bioprinted vasculature and endothelium to cooperatively create vessels, enabling tissue perfusion through the scaffold lumen. Using a cuffing microsurgery approach, the engineered tissue is directly anastomosed with a rat femoral artery, promoting a rich host vasculature within the implanted tissue. After two weeks in vivo, contrast microcomputer tomography imaging and lectin perfusion of explanted engineered tissues verify the host ingrowth vasculature's functionality. Furthermore, the hierarchical vessel network (VesselNet) supports in vitro functionality of cardiomyocytes. Finally, the proposed approach is expanded to mimic complex structures with native‐like millimetric vessels. This work presents a novel strategy aiming to create fully‐engineered patient‐specific thick tissue flaps. Abstract : Mesoscale tubular scaffolds and 3D bioprinted vascularized hydrogels are combined to create engineered hierarchically vascularized tissues (engineered flap) consisting of rich microvascular networks in communication with an engineered endothelium. The in vitro cultured flaps are directly anastomosed to the host vasculature, which perfuses the implanted tissue. The concept is expanded by 3D printing patient‐specific vascular constructs with complex native architectures.